Influence of hormone therapy or C. foetida extract on breast tenderness in postmenopausal women. (4th May 2018) - Gao, L.; Zuo, H.; Zheng, T.; Xue, W.; Wang, Y.; Deng, Y.; Sun, A.
Abstract: Objective: To evaluate the prevalence of breast tenderness in a population treated with menopausal hormone therapy (MHT) or Cimicifuga foetida extract. Methods: A prospective, randomized, controlled trial was conducted. Ninety-six postmenopausal women were randomly assigned to three groups: group A, 1 mg estradiol valerate daily plus 4 mg medroxyprogesterone acetate (MPA), days 19–30; group B, 1 mg estradiol valerate daily plus 100 mg micronized progesterone (MP), days 19–30; group C, 100 mg C. foetida extract daily. Breast tenderness was evaluated daily for 12 months. Results: Seventy-three patients completed the study. Group A had the highest prevalence of breast tenderness, while group C had the lowest. More than 50% of all participants reported no symptoms throughout the period. The participants in group A experienced a sharp increase in breast tenderness after treatment, but decreased after 1 month. No significant decline was found in the duration of pain in group B. The patients in group C reported no remarkable changes after 1 month. Compared to estrogen only, estrogen plus MPA/MP led to a higher incidence of prolonged breast symptoms. Conclusions: Compared to MHT groups, C . foetida extract had the lowest prevalence of breast tenderness. Most participants experienced mild or no symptoms.